Strengthening Students’ Disciplined Character through Teachers’ Pedagogical Competence Improvement - Sofiana Ratnasari; Wakhudin Wakhudin (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the levels of students' learning discipline, teachers' pedagogical competency strategies, and their effectiveness in improving students' learning discipline in the Ki Hajar Dewantara Cluster in Pekuncen District. This study employed a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and documentation. Subjects included elementary school teachers and students selected purposively. Data were analyzed through the stages of reduction, presentation, and conclusion drawing using a source triangulation approach. The results indicate that students' learning discipline is considered good, characterized by punctuality, responsibility, and adherence to learning rules. The pedagogical strategies implemented by teachers include habituation, role modelling, and character-oriented motivation. Teachers' pedagogical competency has proven effective in improving students' learning discipline through a reflective approach and a conducive learning environment. The implications of this study emphasize the importance of strengthening pedagogical competency as a primary factor in developing learning discipline in elementary schools. The results also contribute to the development of character education theory and serve as a reference for future policies aimed at improving teacher professionalism.